A re-evaluation of taxonomic status of Montivipera (Squamata: Viperidae) from Iran using a DNA barcoding approach - Rastegar Pouyani, Eskandar; Wink, Michael (Biochemical systematics and ecology, 2014)
Mitochondrial COI sequences were used to re-evaluate the taxonomic status of Montivipera from Iran including all of the known Iranian species. Considering the genetic distances among species, the topology of the phylogenetic trees and principles of species definition, the number of species within the genus Montivipera in Iran should be reduced from four to one species, Montivipera raddei, exhibiting several pretty color patterns. It looks as if superficial differences in morphology and particularly color pattern induced herpetologists in describing species such as Montivipera albicornuta, Montivipera latifii and Montivipera kuhrangica.